Implementasi Metode Tikrar Dalam Menghafal Al-Qur’an Di SMK Swasta Mulia Medan - Aisyah, Siti; Mavianti, Mavianti (EL-EMIR Institute, 2025)
This study aims to describe the implementation of the tikrar method in memorizing the Qur'an at SMK Swasta Mulia Medan Tanjung Sari, Medan Selayang. The tikrar method is a memorization method carried out by continuously repeating verses so that they are embedded in long-term memory. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the tikrar method is very effective in helping children or students memorize the Qur'an, especially with the strategies of repeating memorization after prayer, tasmi' (delivering memorization), and murajaah (repetition of memorization). This method also encourages discipline in time management and forms the habit of repeating memorization at various opportunities. Obstacles encountered include difficulty managing time, similar verses, and psychological factors such as boredom. However, with motivation, a supportive environment, and guidance from the school's tahfidz teacher, all students were able to overcome these challenges and achieve the target of memorizing 30 juz within the desired time frame.